Investigation of Integrated Rectangular SIW Filter and Rectangular Microstrip Patch Antenna Based on Circuit Theory Approach - Zakaria, Zahriladha; Sam, Weng Yik; Abd Aziz, Mohamad Zoinol Abidin; Jawad, Mohamed Saeed; Mohamad Isa, Mohd Sa'ari (International Journal of Advanced Studies in Computers, Science and Engineering, 2012)
This paper presents an investigation based on the resonant circuit approach to characterize an integrated microwave filter and antenna from a lumped element prototype. This approach is used to design an integrated filter and antenna to reduce the overall size of the physical dimensions of the RF/microwave front-end subsystem. This study focuses on the integration of a rectangular Substrate Integrated Waveguide (SIW) filter with a rectangular microstrip patch antenna to produce a filtering and radiating element in a single device. The physical layouts of the SIW filter and rectangular microstrip patch antenna based on single- and dual-mode will be developed. To prove the concept, the integrated microwave filter and antenna at a center frequency of 2 GHz is demonstrated and validated through simulation and laboratory experiments. The experimental performance yielded promising results that were in good agreement with the simulated results. This study is beneficial for microwave systems, given that the reduction of the complexity of design and physical dimension as well as cost are important for applications such as base stations and multiplexers in wireless communication systems.